Prevalence of COVID-19 and Psychotropic Drug Treatment in Psychiatric In-patients in Germany in 2020: Results from a Nationwide Pilot Survey - Mueller, Juliane K.; Ahrens, Kira F.; Bauer, Michael; Baune, Bernhard T.; Borgwardt, Stefan; Deckert, Jürgen; Domschke, Katharina; Ellwanger, Regina; Fallgatter, Andreas; Frodl, Thomas; Gallinat, Jürgen; Gottschalk, René; Grabe, Hans J; Hasan, Alkomiet; Herpertz, Sabine C; Hurlemann, Rene; Jessen, Frank; Kambeitz, Joseph; Kircher, Tilo; Kornhuber, Johannes; Lieb, Klaus; Meyer-Lindenberg, Andreas; Rupprecht, Rainer; Scherbaum, Norbert; Schlang, Christiane; Schneider, Anja; Schomerus, Georg; Thoma, Andreas; Unterecker, Stefan; Walter, Martin; Walter, Henrik; Reif, Andreas; Reif-Leonhard, Christine (Pharmacopsychiatry, 2023)
Introduction In patients with a pre-existing mental disorder, an increased risk for a first manifestation of a psychiatric disorder in COVID-19 patients, a more severe course of COVID-19 and an increased mortality have been described. Conversely, observations of lower COVID-19 incidences in psychiatric in-patients suggested protective effects of psychiatric treatment and/or psychotropic drugs against COVID-19.Methods A retrospective multi-center study was conducted in 24 German psychiatric university hospitals. Between April and December 2020 (the first and partly second wave of COVID-19), the effects of COVID-19 were assessed on psychiatric in-patient care, the incidence and course of a SARS-CoV-2 infection, and treatment with psychotropic drugs.Results Patients (n=36,322) were admitted to the hospitals. Mandatory SARS-CoV-2 tests before/during admission were reported by 23 hospitals (95.8%), while 18 (75%) conducted regular testing during the hospital stay. Two hundred thirty-two (0.6%) patients were tested SARS-CoV-2-positive. Thirty-seven (16%) patients were receiving medical treatment for COVID-19 at the psychiatric hospital, ten (4.3%) were transferred to an intermediate/intensive care unit, and three (1.3%) died. The most common prescription for SARS-CoV-2-positive patients was for second-generation antipsychotics (n=79, 28.2%) and antidepressants (SSRIs (n=38, 13.5%), mirtazapine (n=36, 12.9%) and SNRIs (n=29, 10.4%)).Discussion Contrary to previous studies, our results showed a low number of infections and mortality in SARS-CoV-2-positive psychiatric patients. Several preventive measures seem effective to protect this vulnerable group. Our observations are compatible with the hypothesis of a protective effect of psychotropic drugs against COVID-19 as the overall mortality and need for specific medical treatment was low.
Keywords: COVID-19; psychiatry; psychotropic drugs; SARS-CoV-2